Causes of Obstipation and Its Effects on Health - Navickaitė, Martyna Emilija; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2022)
This article presents a literature review on essential principles of the digestive tract, causes of obstipation, diagnostic and treatment methods.Objective. Analyze the causes of constipation and health problems experienced by people with obstipation.Methods. Scientific articles in PubMed, Mendeley, ScienceDirect and Google scholar databases were analyzed. In the search box key words were used: obstipation, constipation, causes, prophylactic means. 25 full scientific articles in Lithuanian and English from years 2008 – 2022 were analyzed.Results and conclusions. Most common causes of functional obstipation: lack of physical activity, insufficient fluid intake, infrequent consumption of high-fiber food, psychological factors. Obstipation can be diagnosed by anorectal manometry, defecography, baloon expulsion test. Chronic or long-term constipation can lead to complications. Laxatives, anterograde enemas are used for the treatment, an althernative effective treatment method – sacral nerve stimulatiomn.
Keywords: obstipation; constipation; causes; prophylactic means